Efficient sulfur-resistant and water-resistant CO oxidation catalyst and preparation method thereof
Through the Cu-OMS-2 catalyst and NaOH treatment method, the inactivation problem of existing CO oxidation catalysts under interference from SO2 and water vapor is solved, efficient removal of CO and improved anti-toxicity, and the catalyst is maintained during reuse. 80% efficiency, suitable for environmentally friendly treatment of sintered flue gas.
Patent Information
- Application Number
- CN202311706551.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing CO oxidation catalysts are inactivated under interference from SO2 and water vapor in the sintered flue gas, resulting in poor CO removal efficiency and affecting the environmental development of the steel industry.
Using Cu-OMS-2 catalyst and treated with NaOH solution, the catalyst's anti-sulfur and water resistance properties include dissolving potassium permanganate in deionized water, adding concentrated nitric acid, copper nitrate and manganese nitrate, and impregnating it in hydrogen after reaction. In the sodium oxide solution, a high-efficiency anti-sulfur and water-resistant CO oxidation catalyst is prepared after drying, calcining and sieving.
The catalyst's ability to remove CO and anti-toxicity are significantly improved, the catalytic oxidation efficiency reaches 95%, and the catalytic effect is maintained at 80% under the interference of sulfur dioxide and water vapor, supporting the reuse and stable performance of the catalyst.
Smart Images

Figure CN119114094A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst and a preparation method thereof. Background Art
[0002] As a pillar industry in my country, steel production accounts for half of the world's total production. During the sintering process, the air leakage rate is high, and a large part of the air cannot participate in the reaction, which will greatly increase the amount of sintering flue gas. The carbon monoxide concentration of sintering flue gas can reach several thousand mg / m 3 The ambient air quality standard issued by my country states that the 24-hour CO concentration limit is 4 mg / m 3 Flue gas is mainly composed of carbon monoxide (CO), sulfur dioxide (SO2), water vapor, etc. It is a complex pollution of toxic substances. The harm to the human body ranges from acute poisoning to death.
[0003] Therefore, CO removal is easily affected by SO2 and water vapor in the flue gas, resulting in catalyst deactivation and poor CO removal efficiency. Therefore, effectively controlling the CO concentration in sintering flue gas is of great significance to the development of my country's healthy and environmentally friendly steel industry.
[0004] The invention patent with application number 202310427755.9 discloses a sulfur-resistant and water-resistant CO oxidation catalyst and a preparation method thereof. The patent uses potassium permanganate, deionized water, concentrated nitric acid and manganese nitrate as raw materials to prepare OMS-2 powder; then alkaline earth metal salt solution is added to mix and prepare OMS-2 powder solution; finally, the OMS-2 powder solution is heat-treated to obtain a sulfur-resistant and water-resistant CO oxidation catalyst, but the working principle of the invention is different from that of the present application. Summary of the invention
[0005] In view of this, the present invention provides a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst and a preparation method thereof. The catalyst is based on Cu-OMS-2 with good sulfur and water resistance. Through simple NaOH solution treatment, the performance of the catalyst in removing CO is greatly enhanced, and the anti-poisoning ability of the catalyst is improved.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] A method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst comprises the following steps:
[0008] (1) dissolving potassium permanganate in deionized water, then sequentially adding concentrated nitric acid, copper nitrate and manganese nitrate, stirring evenly and reacting to obtain a reacted liquid;
[0009] (2) subjecting the liquid after the reaction in step (1) to solid-liquid separation, and washing to neutrality to obtain separated solid and liquid;
[0010] (3) immersing the solid in step (2) in a container containing a sodium hydroxide solution, sealing the container and reacting the container to obtain a reacted mixture;
[0011] (4) The mixture after the reaction in step (3) is subjected to solid-liquid separation and washed to neutrality, and then the separated solid is dried, ground, calcined, pressed, crushed and sieved in sequence to obtain a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst.
[0012] Preferably, the ratio of potassium permanganate, concentrated nitric acid, copper nitrate and manganese nitrate in step (1) is 0.02-0.03 mol: 1-1.3 mL: 3.5-4.0 mmol: 0.02-0.03 mol.
[0013] Preferably, the concentration of concentrated nitric acid in step (1) is 14-18 mol / L.
[0014] Preferably, the stirring time in step (1) is 20 to 40 minutes.
[0015] Preferably, the reaction temperature in step (1) is 75-85° C., and the reaction time is 20-24 h.
[0016] Preferably, the concentration of the sodium hydroxide solution in step (3) is 0.5-2 mol / L.
[0017] Preferably, the reaction temperature in step (3) is 25-50°C, and the reaction time is 4-6h.
[0018] Preferably, the drying temperature in step (4) is 75-85° C. and the drying time is 10-12 h.
[0019] Preferably, in step (4), the calcination temperature is 350-450° C., the calcination time is 4-6 h, the heating rate during the calcination process is 2-5° C. / min, and the sieving is performed to 40-60 mesh.
[0020] Another object of the present invention is to provide a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst prepared by the above method.
[0021] Compared with the prior art, the present invention has the following beneficial effects: the present invention uses a sodium hydroxide solution of a specific concentration to simply treat Cu-OMS-2, which greatly enhances the ability of the catalyst to remove CO and improves the anti-poisoning ability of the catalyst. After 4 hours of reaction, the catalyst has an efficiency of catalytic oxidation of carbon monoxide of 95%; the catalyst after the reaction is treated again with a NaOH solution and reused, and it is found that the catalyst reused for the second time still has a catalytic effect of nearly 80% after 4 hours of reaction, indicating that the catalyst prepared by the present invention can not only effectively remove carbon monoxide in flue gas, but also can be reused and has stable catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the X-ray diffraction pattern of the catalysts prepared in Examples 1-3 of the present invention and Comparative Example 1;
[0023] Figure 2 It is the X-ray diffraction pattern of the catalyst prepared in Example 4-5 of the present invention and Cu-OMS-2-1M-normothermia;
[0024] Figure 3 The scanning SEM images of Example 4 and Comparative Example 1 of the present invention and the Mapping image of Mn, O, Na and Cu in Example 4 are shown;
[0025] Figure 4 It is a performance diagram of CO removal of the catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 under the interference of sulfur dioxide and water vapor in actual flue gas;
[0026] Figure 5 It is a performance diagram of CO removal of the catalysts prepared in Examples 1, 4 and 5 of the present invention under the interference of sulfur dioxide and water vapor in actual flue gas;
[0027] Figure 6 This is the test result of the sulfur resistance performance of the catalyst prepared in Example 4 of the present invention;
[0028] Figure 7 This is the test result of the water resistance of the catalyst prepared in Example 4 of the present invention;
[0029] Figure 8 The catalyst prepared in Example 4 of the present invention is subjected to repeated experimental tests to simulate the interference of sulfur dioxide and water vapor in actual flue gas. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0031] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0032] Example 1
[0033] A method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst comprises the following steps:
[0034] (1) At room temperature, weigh 0.02 mol potassium permanganate and dissolve it in 80 ml deionized water. Use a magnetic stirrer to fully dissolve it. After 10 minutes, add 1 ml of 16 mol / L concentrated nitric acid to form an acidic environment, then add 3.5 mmol copper nitrate and stir again for 10 minutes using a magnetic stirrer. Finally, add 0.02 mol manganese nitrate, stir evenly, wrap the mouth of the beaker with plastic wrap, and place it at 80° C. for reaction for 24 hours to obtain a liquid after the reaction;
[0035] (2) subjecting the liquid after the reaction in step (1) to solid-liquid separation, and washing to neutrality to obtain separated solid and liquid;
[0036] (3) placing the solid in step (2) into a beaker, then adding 100 ml of 1 mol / L sodium hydroxide solution, wrapping the beaker mouth with plastic wrap, and then placing the beaker in an oil bath to react at room temperature for 5 hours to obtain a reacted mixture;
[0037] (4) The mixture after the reaction in step (3) is subjected to solid-liquid separation, washed to neutrality, placed in a drying oven at 80° C. for drying overnight, and then the dried material is fully ground and then placed in a muffle furnace for calcination. The calcination temperature is 400° C., the calcination time is 5 h, and the heating rate of the calcination process is 2-5° C. / min. The calcined catalyst is pressed, crushed, and sieved to 40-60 mesh to obtain a high-efficiency sulfur-resistant and water-resistant CO oxidation catalyst.
[0038] Example 2
[0039] The difference from Example 1 is that the concentration of the sodium hydroxide solution in step (3) is 0.5 mol / L, and the other conditions are exactly the same as those in Example 1.
[0040] Example 3
[0041] The difference from Example 1 is that the concentration of the sodium hydroxide solution in step (3) is 2 mol / L, and the other conditions are exactly the same as those in Example 1.
[0042] Example 4
[0043] The difference from Example 1 is that the reaction temperature in step (3) is 40° C., and the other conditions are exactly the same as in Example 1.
[0044] Example 5
[0045] The difference from Example 1 is that the reaction temperature in step (3) is 50° C., and the other conditions are exactly the same as in Example 1.
[0046] Comparative Example 1
[0047] The difference from Example 1 is that no sodium hydroxide solution is used, and other conditions are exactly the same as those in Example 1.
[0048] The performance tests were performed on the catalysts prepared in Examples 1-5 and Comparative Examples:
[0049] 1) The X-ray diffraction patterns of the catalysts prepared in Examples 1-5 and Comparative Example 1 are as follows: Figure 1 and Figure 2 As shown by Figure 1 and Figure 2 It can be seen that the diffraction peaks of Cu-OMS-2 modified by sodium hydroxide are still consistent with those in the standard PDF card of Cu-OMS-2 (JCPDS29-1020), indicating that the modification treatment of sodium hydroxide did not change the crystal structure of Cu-OMS-2. No characteristic diffraction peaks of Cu, Cu2O, CuO or other impurity phases were observed in the XRD spectrum, which indicates that the dispersion of Cu ions is good, and it is also possible that Cu ions enter the OMS-2 tunnel;
[0050] The scanning SEM images of the catalysts prepared in Comparative Example 1 and Example 4 are as follows: Figure 3 a and Figure 3 As shown in b, Figure 3 a and Figure 3 b shows that the obtained catalysts are all slender and disordered rod-like structures. Figure 3 a and Figure 3 In b, it was also found that the morphology of Cu-OMS-2 was not significantly affected by the treatment with NaOH. Figure 3 c. Figure 3 d. Figure 3 e and Figure 3 f shows that Mn, O, Na, and Cu elements are well dispersed on the catalyst surface.
[0051] 2) Under the interference of sulfur dioxide and water vapor in the simulated actual flue gas, the CO removal performance of the catalyst samples prepared in Examples 1 to 3 and Comparative Example 1 was evaluated. The test conditions were: total flow rate of 200 mL / min, CO content of 5000 ppm, oxygen content of 15%, humidity of 15%, SO2 content of 50 ppm, reaction temperature of 250°C. The test results are as follows: Figure 4 shown. Figure 4 The results show that in the atmosphere of simulated sintering flue gas, Cu-OMS-2 treated with NaOH concentrations of 0 mol / L, 0.5 mol / L, 1 mol / L, and 2 mol / L shows that the catalytic activity of the catalyst can be significantly improved by NaOH treatment, and its treatment concentration shows a trend of first promoting and then inhibiting the catalytic oxidation of CO. Through repeated experiments, it can be concluded that when the NaOH concentration is 1 mol / L, Cu-OMS-2 still exhibits excellent catalytic activity under the interference of sulfur dioxide and water vapor.
[0052] 3) Under the interference of sulfur dioxide and water vapor in simulated actual flue gas, the CO removal performance of the catalyst samples prepared in Examples 1, 4, and 5 was evaluated respectively. The test conditions were: total flow rate of 200 mL / min, CO content of 5000 ppm, oxygen content of 15%, humidity of 15%, SO2 content of 50 ppm, and reaction temperature of 250°C. The test results are as follows: Figure 5 shown.
[0053] Figure 5 It shows that based on the optimal NaOH concentration, the effect of reaction temperature on the treatment of Cu-OMS-2 with NaOH was investigated, and the catalyst was treated with 1 mol / L NaOH at room temperature, 40°C, and 50°C to test its activity. The results show that the treatment of Cu-OMS-2 with NaOH at 40°C can show better catalytic activity, achieve efficient removal of CO under sintering flue gas conditions, and has good anti-sulfur and anti-water properties.
[0054] 4) The sulfur resistance performance of the catalyst sample prepared in Example 4 was evaluated under the following test conditions: total flow rate of 200 mL / min, CO content of 5000 ppm, oxygen content of 15%, SO2 content of 50 ppm, and reaction temperature of 250°C. The test results are shown in Figure 6 shown.
[0055] Figure 6It shows that within 90 minutes of passing SO2, the catalyst can maintain 100% efficiency, but as the reaction proceeds, the catalyst begins to be poisoned, which may be due to the chemical adsorption of sulfur dioxide on the catalyst surface, thereby destroying the active sites on the catalyst surface. After about 4.5 hours of reaction, the efficiency of the catalyst in catalyzing CO dropped to 60%. At this time, the catalytic activity did not improve when the SO2 was stopped, and it remained at the current level, indicating that sulfur dioxide caused irreversible poisoning of the catalyst.
[0056] 5) The water resistance of the catalyst sample prepared in Example 4 was evaluated under the following test conditions: total flow rate of 200 mL / min, CO content of 5000 ppm, oxygen content of 15%, humidity of 15%, and reaction temperature of 250°C. The test results are shown in Figure 7 shown.
[0057] Figure 7 It shows that Example 4 has good water resistance. Under the condition of simulating the water content in actual sintering flue gas (15 vol% H2O), the catalyst can still maintain 100% catalytic effect after 50 hours of reaction, indicating that the catalyst treated with NaOH can effectively prevent the negative influence of water vapor in the flue gas on its catalytic oxidation of CO and has good long-term stability.
[0058] 6) The catalyst sample prepared in Example 4 was tested repeatedly under the following conditions: total flow rate of 200 mL / min, CO content of 5000 ppm, oxygen content of 15%, humidity of 15%, SO2 content of 50 ppm, and reaction temperature of 250°C. The test results are shown in Figure 8 shown.
[0059] Figure 8 It shows that: under the interference of sulfur dioxide and water vapor in the simulated actual flue gas, the reaction is carried out using Example 4, and it is recovered. The catalyst is added to 100ml of NaOH solution with a concentration of 1mol / L, and the beaker is wrapped with plastic wrap. The beaker is placed in an oil bath pot and reacted for 5h at 40℃. The sample obtained after the reaction is completed is separated from the solid and liquid and washed to neutrality, placed in a drying oven at 80℃ for overnight drying, and fully ground. It is placed in a muffle furnace for calcination, and the calcined catalyst is pressed, crushed, and sieved to 40-60 mesh again, and the catalytic reaction is carried out again. It is found that the catalyst still has a catalytic effect of 90% after the reaction for 4 hours. Repeat the above experiment and reuse it for the second time. It is found that the catalyst reused for the second time can still have a catalytic effect of nearly 80% after the reaction for 4 hours. It provides a new solution for removing CO in practical applications and lays a foundation for the recycling of resources.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst, characterized in that: The following steps are involved: (1) dissolving potassium permanganate in deionized water, then sequentially adding concentrated nitric acid, copper nitrate and manganese nitrate, stirring evenly and reacting to obtain a reacted liquid; (2) subjecting the liquid after the reaction in step (1) to solid-liquid separation, and washing to neutrality to obtain separated solid and liquid; (3) immersing the solid in step (2) in a container containing a sodium hydroxide solution, sealing the container and reacting the container to obtain a reacted mixture; (4) The mixture after the reaction in step (3) is subjected to solid-liquid separation and washed to neutrality, and then the separated solid is dried, ground, calcined, pressed, crushed and sieved in sequence to obtain a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst.
2. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The ratio of potassium permanganate, concentrated nitric acid, copper nitrate and manganese nitrate in step (1) is 0.02-0.03 mol: 1-1.3 mL: 3.5-4.0 mmol: 0.02-0.03 mol.
3. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The concentration of concentrated nitric acid in step (1) is 14-18 mol / L.
4. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The stirring time in step (1) is 20 to 40 minutes.
5. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The reaction temperature in step (1) is 75-85° C. and the reaction time is 20-24 h.
6. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (3) is 0.5-2 mol / L.
7. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The reaction temperature in step (3) is 25-50°C and the reaction time is 4-6h.
8. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: The drying temperature in step (4) is 75-85° C. and the drying time is 10-12 hours.
9. The method for preparing a highly efficient sulfur-resistant and water-resistant CO oxidation catalyst according to claim 1, characterized in that: In step (4), the calcination temperature is 350-450° C., the calcination time is 4-6 hours, the heating rate during the calcination process is 2-5° C. / min, and the sieving is performed to 40-60 mesh.
10. A highly efficient sulfur and water resistant CO oxidation catalyst, characterized in that: Prepared according to any one of claims 1 to 9.
